Gender favoritism in derogatory and non-derogatory political discourse - Manuel Hons; Edgar Onea; Silvia Erika Kober (PLoS ONE, 2026)
This study investigates the interplay between Role Congruity Theory and Social Identity Theory in the context of gender perceptions among political speakers. Role Congruity Theory posits that male political speakers are perceived as more competent and likable, regardless of the recipient’s gender. Conversely, Social Identity Theory suggests that individuals may exhibit a preference for speakers of the same gender due to in-group identification. We hypothesized that male participants would demonstrate a consistent preference for male speakers, driven by the synergistic effects of Role Congruity Theory and Social Identity Theory, while female participants would exhibit no such bias, resulting from the cancellation of these effects. To test this hypothesis, participants assessed German words for their offensiveness and political connotation. We employed generalized linear mixed effects models to analyze the data for two response variables – pejorative weight and political connotation – across four distinct word clusters: politically left & less derogatory, politically right & less derogatory, politically left & derogatory, and politically right & derogatory. Our findings indicate that, in terms of pejorative weight, derogatory language elicited a tendency towards in-group favoritism, which we interpret as a protective mechanism for social identity. This effect contrasts with the broader trend of male favoritism identified in other contexts. These results contribute to a deeper understanding of how gender dynamics shape the interpretation of political language, highlighting the complex interactions between social identity and speech perception in political discourse.